Construction of multi-robot platform based on dobot robots - Han, Jinchi; Ma, Duojicairang (Frontiers in Neurorobotics, 2025)
For the researches of cooperative control scheme for multirobot systems, this paper sets up an experimental platform based on dobot robots, which can be used to perform physical experiments to verify related schemes. A distributed scheme is proposed to achieve cooperative control for multirobot systems. Simulation results prove the effectiveness of the distributed scheme. Then, the experimental platform based on dobot robots is built to verify the proposed scheme. Specifically, a computer sends data to the microcontroller inside the host through WiFi communication, then the host distributes data to the slaves. Finally, the physical experiment of related schemes is performed on the experimental platform. Comparing the simulations with the physical experiments, the task is successfully completed on this experimental platform, which proves the effectiveness of the scheme and the feasibility of the platform. The experimental platform developed in this paper possesses the capability to validate various schemes and exhibits strong expandability and practicality.